A Rare Case of Disseminated Mycobacterium avium-intracellulare Presenting as Proctitis. (3rd December 2019) - Chime, Chukwunonso; Bhandari, Peter; Niazi, Masooma; Patel, Harish
Abstract : Mycobacterium avium intracellulare (MAI) infections are common in Human Immuno-deficiency Virus (HIV) positive patients. MAI infection can have localized or disseminated presentation, patients with low CD4 count presenting with disseminated infection. Fever, abdominal pain, diarrhea, and weight loss are generally the presenting symptoms of disseminated MAI. We present a rare case of a patient with HIV and low CD4 count presenting with proctitis as manifestation of disseminated MAI infection. A 25 year-old-man with HIV came to the emergency room (ER) with complaints of intermittent rectal bleeding for two months. His CD4 count was less than 20 cells/ µ L. He was MSM (men having sex with men) and has receptive anal intercourse with men. His stool work-up was unrevealing for infectious etiology. Swabs for gonorrhea and chlamydia were negative. Colonoscopy revealed erythematous, congested, friable rectal mucosa with two superficial ulcers. Biopsies of the ulcer were positive for acid fast staining bacteria and the culture grew MAI. His blood culture was negative for growth of acid-fast bacteria (AFB). However, liver biopsy performed for elevated alkaline phosphatase of 958 units/L revealed noncaseating granuloma. Gastro-duodenoscopy with duodenal biopsy did not reveal any mucosal abnormality. He was managed as with disseminated MAI infection using clarithromycin, ethambutol, and rifabutin in addition to HAART therapy. Interval Colonoscopy in 20 months showed resolution of rectal ulcer. The gut is often involved in patients with disseminated MAI infection, with the duodenum being the most common site. MAI infection should be suspected as possible etiology for proctitis in HIV positive patient with low CD4 count, as proctitis, though infrequent can be the sole presentation for disseminated MAI infection in patients with HIV and low CD4 count.